Advanced ASP.NET Core 3.1 MVC - Patel, Bhrugen (Packt Publishing, 2020)
Build real-world MVC applications using Repository Pattern, N-Tier Architecture, APIs, Entity Framework Core and ASP.NET MVC Core 3.1 About This Video Discover the structure and basic security of the ASP.NET Core 3.1 MVC project Explore the Repository Pattern and N-Tier Architecture, which are commonly used in the professional world Build applications with ASP.NET Core 3.1 using MVC In Detail Whether you're looking to understand the Repository Pattern and N-Tier Architecture or get to grips with data seeding and deployment to Azure, this course will equip you with the knowledge you need. You'll start by understanding the Repository Pattern and the N-Tier Architecture. The next section will then guide you through integrating the Identity framework. In addition to this, you'll understand how to add more fields to users. As you progress, the course will help you focus on authorization and authentication in ASP.NET Core 3. By the end of this book, you will be equipped with the knowledge you need to develop real-world MVC apps confidently using the N-Tier Architecture, Entity Framework Core, and ASP.NET MVC Core 3.1.